2019
DOI: 10.1097/md.0000000000016436
|View full text |Cite
|
Sign up to set email alerts
|

Grade-lymph node ratio predicts the survival of breast cancer in different molecular types

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The LNR has been reported to be a significant prognostic factor in the survival of BC patients in many recent studies [13][14][15][16], and some studies have also reported that the LNR is superior to traditional pN stage in predicting BC prognosis. Currently, NAC is broadly used in the systematic treatment of BC.…”
Section: Discussionmentioning
confidence: 99%
“…The LNR has been reported to be a significant prognostic factor in the survival of BC patients in many recent studies [13][14][15][16], and some studies have also reported that the LNR is superior to traditional pN stage in predicting BC prognosis. Currently, NAC is broadly used in the systematic treatment of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of ACC1 activity abrogated the dissemination of 4T1 murine breast cancer cells to the lung (29). Indeed, accumulating evidence suggests that extensive lymph node metastasis is associated with poor prognosis, as well as short overall and disease-free survival of patients with breast cancer (30,31). In this study, the role of HLCS in supporting cell invasion was demonstrated in the MCF-7 cell line in which suppression of HLCS expression resulted in 40-50% reduction of cell invasion through extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Increased lymph node ratio has been repeatedly shown to predict long-term survival in various cancers. 68,12 Selecting patients for adjuvant therapy based on lymph node ratio, or evaluating impacts of lymph node ratio on adjuvant therapy effectiveness, has been studied for others cancers like gastric, 27 pancreatic, 28 and esophageal. 29 As for colon cancer, Moug et al considered the value in lymph node ratio for staging colon cancer, and its implications on determining which patients would benefit from adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…5 A number of observational studies have demonstrated that lymph node ratio to be a prognostic factor for other cancers such as head-and-neck, 6 esophageal, 7 and breast. 8 These findings are also reflected in numerous colorectal cancer observational studies examining lymph node ratio and long-term survival. 911 However, there is no consensus regarding the extent to which different lymph node ratio cut-off values predict long-term survival and how to use this value in conjunction with overall lymph node harvest.…”
Section: Introductionmentioning
confidence: 86%